(untitled) (International Journal of Food and Nutritional Sciences, 2022)
Expectations from the women are increasing as society goes advance. Now days, women are not only play the role of home maker but also they can generate income for their family by joining the organization as a paid workforce. The main reason for maximum number of women are working women, is change in the mindset of new generation and increasing cost of living. In recent time, women are the equal competitor of man in each and every field. So this tendency is increased day by day, as a result, dual career families replaced by the core traditional families. Women are facing difficulties to maintain work life balance as they have higher workload and dual responsibility of work and home. In the current study, 135 women educators working in higher education are considered for the survey. It is concluded from the current study that the level of work life balance is moderate. It can be enhance by providing the Flexible working hours, child care facility, Transport facility, Recreational facilities and Job sharing.